Adaptation and Diversification in Bluebells (Mertensia spp., Boraginaceae) - Lin, Shang-Yao Peter (Université d'Ottawa / University of Ottawa, 2019)
Examining the ecological processes generating evolutionary patterns is crucial to understanding how biodiversity arises and evolves. One of the most striking examples of evolutionary diversification is provided by the flowering plants (angiosperms) and their flowers. Pollinators are traditionally considered to be the most important selective agents and drivers of floral diversity. However, many angiosperms have a generalized floral morphology and are visited by a diverse and overlapping suite of pollinators, making it unclear how pollinators could have driven diversification in these taxa. In addition, flowers and plant reproductive success are likely to be influenced by factors other than pollinators, such as herbivores, precipitation, and temperature. These factors need to be considered along with pollinators in order to improve our understanding of angiosperm evolution and diversification. In my thesis, I focussed on the processes influencing adaptation and diversification in flowering plants in the genus Mertensia (Boraginaceae), which have relatively unspecialized flowers that attract a variety of nectar- and pollen-feeding insects. In Chapter One, I explored correlations among floral traits, vegetative traits, and flowering phenology across 12 Mertensia species. In Chapter Two, I assessed reproductive isolating barriers between related Mertensia species occurring in sympatry. In Chapter Three, I examined the ecological function of floral orientation in two Mertensia species with respect to pollinators and precipitation. First, across Mertensia species, I found that early-flowering species were shorter, produced fewer flowers, and occurred at higher altitudes than late-flowering species—suggesting a life-history trade-off between plant size and flowering phenology, as well as an altitudinal effect on both traits. Interspecific variation in floral traits was not strongly associated with variation in flowering phenology or plant size. Second, between sympatric M. brevistyla and M. fusiformis populations, I found weak reproductive isolating barriers and possible hybridization. Most pre-pollination barriers were weak, as the two Mertensia species shared similar habitats, flowering phenology, and pollinator assemblages. The two relatively strong barriers were floral (ethological and mechanical) isolation and post-pollination isolation: Pollinators transferred significantly more of a pollen analogue among conspecific than heterospecific plants in mixed-species arrays, and flowers yielded higher seed set when receiving conspecific rather than heterospecific pollen in hand-pollination experiments. Lastly, I found that floral orientation was more likely to be under selection by precipitation than by pollinators, in that paternal fitness (i.e., pollen germination) was reduced by contact with water and that pollinator-mediated selection via maternal fitness (i.e., seed set) was not detected. A more pendant floral orientation likely protects the relatively long and exposed anthers of M. fusiformis from rain, while the less pendant M. brevistyla does not require this protection because of its shorter, more concealed reproductive structures. Although I detected an effect of floral orientation on seed set, I was not able to identify the selective agents driving this effect. In summary, my results suggest that pollinators play a minor role in influencing floral adaptation and diversification in Mertensia. Instead, the dominant influences on the traits I examined appear to be life-history trade-offs, environmental conditions that vary along altitudinal gradients, and abiotic variables (e.g., precipitation). It is important to consider these factors and their influences on paternal and maternal fitness in order to gain a broader perspective on floral evolution in plants with generalized pollination systems.
Keywords: Mertensia; Boraginaceae; diversification; flowers; life-history; reproductive isolation; selection